Imágenes sialográficas parotídeas en individuos con alcoholismo crónico - Julio Ramirez-C; Rafael Romo-E; Alfredo Esguep-S; Gloria Cecilia Cossio-M (Universidad de Antioquia, 1996)
Sialographic images of the parotid gland in 60 pat.. suffering from ohmic alcoholism were compared with the corn. ding sialographic study of 40 controls ranging from ages 15 to 55 years old. Results s..ved a decrease in secondary duct dia..er, which it usually observed in healthy subject and confered a duct find.m aspect to the sidographu image of parotid gland filling. Itis possible to conclude that this type of image may ind to tlluu diagnosis /chrome alcoholism.